Speed characteristics of jumpers in a running triple jump - Salamatov M.B. (Theory and Practice of Physical Culture, 2024)
Increasing competitive results is a hot topic for specialists and athletes in any sport. This study analyzes previously obtained data on horizontal jumps. An assessment was also made of the speed capabilities of the best Russian triple jump jumpers, and the dependence of the quantitative values of the speed realization coefficient and the speed difference in the last and penultimate 5-meter run-up sections for highly qualified jumpers was experimentally proven. The work provides an assessment of the speed parameters of training runs with and without push-off. A comparative analysis of the performance of training and competition runs made it possible to identify differences in the speed characteristics and efficiency of jumping techniques of jumpers. As a result of the study, it was found that the best Russian triple jumpers have significant speed capabilities, which they successfully implement during competitive run-ups. The coefficient of speed realization and the difference in speed in the last sections of the run-up turned out to be significant indicators reflecting the efficiency of the jump and the level of training of the athletes. It is also worth noting that the preparation of jumpers for take-off significantly affects their speed characteristics. Analysis of training runs showed that the lack of take-off affects the jumper’s speed drop. This demonstrates the importance of proper take-off technique and its impact on overall jump performance. In general, the study allows us to better understand the speed capabilities of triple jump jumpers, as well as the influence of preparation and various factors on the results of the competition. The data obtained can be useful for coaches and athletes, helping them optimize training programs and jumping technique in order to achieve the highest results.